NATO & Iraq: Factis Non Verbis - Schake, Kurt W. (2005)
This is a thematic report that assesses several prominent aspects of NATO and the possibility of expanding its operations in Iraq. It begins with an examination of the Alliance's political context, to discuss the concept of consensus, central tenets of the NATO charter, the debate over "out-of-area" military action, and high-level decisions on Iraq made by the North Atlantic Council. Next, energy resources (oil and natural gas) are examined, to present the prominence of the Persian Gulf region, dependencies within the economies of NATO nations, and the impact of regional instability on the worldwide prices of these fluid fossil fuels. The author, a former NATO requirements officer, then examines the Alliance's military forces, to show defense expenditures, force structures, and operational experience, which reveal tremendous capabilities and an available pool of forces. Iraq is then discussed, to show potential locations and missions that could be conducted by a NATO-led division. Essentially, this is a positive, but prodding story. The Alliance has overcome the divisive period of early 2003, reached unanimous agreement on a number of contentious issues, and has begun to formally contribute resources to important tasks within Iraq. However, the Alliance has significant political, economic, and military interests in the successful rebuilding of Iraq and, as such, should be formally contributing to broader missions in the country. This is a defining period for the newly expanded, post-Cold War Atlantic Alliance. NATO has the interests, capability, and obligation to do much more in Iraq. The very relevance of the Alliance is at stake.